Childbirth education: module utilizing mothers for father-infant attachment during deployment - Rinaldi, Sabrina M. (Kansas State University, 2018)
Childbirth has an effect on an individual and family. In Western culture, the presence of fathers is expected at labor and birth. The role fathers play during pregnancy, labor and birth, and postpartum is ambiguous. Paternal and infant attachment are developed during this transition to parenthood. There are many choices and unexpected outcomes but through childbirth education, individuals and families can be empowered to have a satisfying experience, ultimately setting the family up for success. Military individuals and families have unique and often challenging obstacles when it comes to participation in childbirth. Utilizing education developed to address concerns military individuals and families might face can lead to an empowering and satisfying experience, and help family bonds during a deployment. A module was created to bridge the gap in childbirth education, specifically for military families facing deployment. The module was developed to supplement existing childbirth education curriculum and is divided into three subsections: pregnancy, labor and birth, and postpartum.
Keywords: Father-infant attachment; Military deployment; Childbirth education; Military fathers